2021
DOI: 10.1016/j.paid.2020.110426
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related stress and anxiety are associated with negative body image in adults from the United Kingdom

Abstract: The stress and anxiety caused by the coronavirus (COVID-19) pandemic presents a serious threat to psychological well-being in populations worldwide and may also extend to body image outcomes. To test this hypothesis, we conducted a preliminary study in which an online sample of adults from the United Kingdom ( N = 506, age M = 34.25 years) were asked to complete measures of perceived stress, stressful life events, trait anxiety, COVID-19-related stress and anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(121 citation statements)
references
References 26 publications
6
110
3
2
Order By: Relevance
“…The total scores range from 0 to 40, with higher scores showing higher levels of perceived stress. In this study, the Cronbach's α was very good (α = 0.883), similar to that in previous studies that used this same tool [35,36].…”
Section: Perceived Stress Scalesupporting
confidence: 88%
“…The total scores range from 0 to 40, with higher scores showing higher levels of perceived stress. In this study, the Cronbach's α was very good (α = 0.883), similar to that in previous studies that used this same tool [35,36].…”
Section: Perceived Stress Scalesupporting
confidence: 88%
“…33 Moreover, another study reported an association between COVID-19-related stress negative body image in adults. 34 The subsequent increase of interest in cosmetic procedures such as botulinum toxin injections, dermaroller, and chemical peeling may also be explained by these findings. Another possible explanation is the exacerbation of acne and rosacea induced by the use of protective masks.…”
Section: Discussionmentioning
confidence: 97%
“…While these prevention measures can be effective against disease transmission [e.g. (Tian et al 2020 )], the impact of lockdowns—and the resulting changes in behaviour patterns and functioning—on emotional well-being is likely to be substantive (Fiorilo and Gorwood 2020 ; Galea et al 2020 ; Swami et al 2021 ; Torales et al 2020 ). Indeed, emerging evidence from other nations indicates that lockdown measures have led to increases in depressive symptoms, anxiety, and severe stress [e.g., (Gao et al 2020 ; Newby et al 2020 ; Qiu et al 2020 ; Tull et al 2020 ; Wang et al 2020 ); for a review, see (Brooks et al 2020 )], which is consistent with the findings of earlier studies on the psychological consequences of other pandemics [e.g., (Hawryluck et al 2004 ; Wheaton et al 2012 )].…”
Section: Introductionmentioning
confidence: 99%